Clinical Classifications of Children With Psychogenic Non-epileptic Seizure - Zhang, Li-Ping; Jia, Yu; Huang, Hao; Li, Da-Wei; Wang, Yu-Ping (Frontiers in Pediatrics, 2021)
Objective: To analyze the clinical features of children with psychogenic nonepileptic seizures in one tertiary center in China. Methods: Clinical data including medical records and video- electroencephalograph (video-EEG) monitoring records of 88 pediatric PNES patients hospitalized in the pediatric department of Xuanwu Hospital, Beijing, China from April.2012 to April.2018 were collected in this study. Demographic information of patients, semiological classification, duration and frequency of symptoms, risk factors as well as comorbidity were summarized and analyzed. Results：For semiological classification, all PNES related symptoms were divided into different categories: motor symptoms, unresponsiveness, sensory symptoms, visceral symptoms, and abnormal behaviors, among which motor symptoms were the most prevalent form. Risk factors were reviewed and categorized into two groups: persistent factors and predisposing factors, and patients were most frequently affected by the influences of families. The duration and frequency of symptoms varied substantially within PNES patients while the average time of duration was relatively longer than epilepsy as reported previously. Epilepsy was considered as the most frequent comorbidity of PNES and PNES patients misdiagnosed as epilepsy often mistreated with antiseizure medication. Significance：Our study showed that motor PNES are the most frequent seizure type. Family issues were a risk factor for PNES. Epilepsy was the most frequent co-existing neurological comorbidity.